2008
DOI: 10.1177/1043659608317451
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cultural Awareness of Nursing Students

Abstract: This pilot study was designed to measure nursing students' level of cultural awareness. It replicated phase II of Rew, Becker, Cookston, Khosropour, & Martinez's (2003) methodological study that developed and tested a Cultural Awareness Scale (CAS). Using a cross-sectional design, the CAS was distributed to nursing students in three nursing programs' (bachelor's, master's, doctoral) beginning and end courses. Cronbach's alpha for the CAS Total instrument was 0.869, with subscale scores ranging from 0.687 to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
21
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
11
21
3
Order By: Relevance
“…These results indicated the questions correlated appropriately within each subscale and were consistent with the findings of Rew et al [14]. This data contributed to the dependability and supported the reliability of the CAS [15]. The statistical data from the previous research and the CAS total instrument reliability of ≥ 0.70, led to the conclusion the instrument was suitable for this study.…”
Section: Reliabilitysupporting
confidence: 79%
See 1 more Smart Citation
“…These results indicated the questions correlated appropriately within each subscale and were consistent with the findings of Rew et al [14]. This data contributed to the dependability and supported the reliability of the CAS [15]. The statistical data from the previous research and the CAS total instrument reliability of ≥ 0.70, led to the conclusion the instrument was suitable for this study.…”
Section: Reliabilitysupporting
confidence: 79%
“…Krainovich-Miller et al [15] reported a Cronbach's alpha for the CAS total instrument of 0.869, with subscale scores ranging from 0.687 to 0.902. These results indicated the questions correlated appropriately within each subscale and were consistent with the findings of Rew et al [14].…”
Section: Reliabilitymentioning
confidence: 99%
“…This scale is originally designed in English (with 36 items) and has been used in several studies for measuring the cultural awareness and cultural competence among nursing students. [32,33] The reliable and validated CAS is also available in Swedish with 35 items. [31] In the Swedish version, one item was removed due to the lack of validity and reliability.…”
Section: Instrumentmentioning
confidence: 99%
“…They were asked to rate statements on a scale of 1 to 4 based on their level of agreement, where 1 represented strongly disagree and 4 represented strongly agree. 17,24,[27][28][29] Raw scores were calculated and then categorized to determine if a student was culturally incompetent (20-44), aware (45-63), competent (64-74), or proficient (75-80). The cumulative score, not the category, was the dependent variable used for analysis.…”
Section: Instrumentationmentioning
confidence: 99%
“…1,13 Researchers have provided many different variations of the definition of cultural competence, but all agree that it is an ongoing process in which individuals gain knowledge, experience, and comfort in dealing with patients who are different from themselves. 11,13,[15][16][17][18][19][20][21][22] Currently, the majority of research on cultural competence is being performed with physicians and nurses. 23 Results of these studies have provided interesting information on current perceptions of cultural competence.…”
Section: Introductionmentioning
confidence: 99%